THU0210 The comparison of childhood polyarteritis nodosa and cutaneous polyarteritis NODOSA. (23rd January 2014) - Demirkaya, E.; Turker, T.; Ruperto, N.; Cuttica, R.; Brogan, P.; Quartier, P.; Anton, J.; Ayaz, N.; Garay, S.; Espada, G.; Khubchandani, R.; Zulian, F.; et al.
Abstract : Background: Polyarteritis nodosa (PAN) is a predominantly medium size vasculitis characterized by non granulomatous necrotizing vasculitis. In children (c-) the disease may be confined to the skin only (cutaneous involvement-PAN) or may present with systemic involvement (systemic c-PAN) as in adult polyarteritis nodosa. Objectives: We aimed to evaluate clinical, laboratory and imaging features of cutaneous c-PAN and the systemic c-PAN form in a large international pediatric vasculitis registry available on the PRINTO database. Methods: We extracted from the PRINTO database all the patients who fulfilled the Ankara 2008-EULAR/PRES/PRINTO criteria for systemic c-PAN. The cutaneous c-PAN patients as per the treating physician diagnosis were also extracted. To define clinical and laboratory characteristics who could help to differentiate cutaneous PAN from cPAN and univariate logistic regression analysis was performed. Results: There were 109 and 45 patients classified as systemic c-PAN, and cutaneous c-PAN respectively with a mean age at diagnosis of 9.47±3.59 years; and 9.12±3.83 years; respectively. The female/male ratio and ethnicity did not differ in the 2 subtypes. The cutaneous group had significantly less constitutional features and less acute phase reactant levels, as expected. The median values (IQR 25-75%) for the ESR and CRP for cPAN were 78 (48-108) mm/h and 7.36 (2.76-15.03) mg/dL. Musculoskeletal features such as myalgia was present in 82 (75.2%) patients with c-PAN and 18 (40.9%) patients with cutaneous PAN (p<0.001) both groups. As differentiating features skin infarcts were observed in c-PAN only and constitutional features, angiographic abnormalities, and organ involvement was not seen in any of the cutaneous PAN patients. Malaise, fever, severe headache, motor mononeuritis multiplex, sensory peripheral neuropathy, abdominal pain, and hematuria were the most statistically significant clinical characteristics able to differentiate these two entities. Conclusions: This is the first study comparing the features of childhood PAN and cutaneous PAN in a large group of pediatric patients. Further biological studies are needed to effectively differentiate the two entities. References: Ozen S, Pistorio A, Iusan SM et al.: EULAR/PRINTO/PRES criteria for Henoch-Schonlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis 2010; 69(5):798-806. Disclosure of Interest: None Declared